"It's Hidden, After All:" A Modified Delphi Study Exploring Faculty and Students' Perceptions of a Graduate Professional Seminar in Communication - Krista Hoffmann-Longtin; Maria Brann; The Professional Seminar Delphi Working Group (Central States Communication Association, 2020)
Graduate student socialization has been studied in multiple disciplines, including communication. As their career trajectories change, faculty must consider how to socialize students into the field and their subsequent careers. Using a modified Delphi survey, we examined the differences in faculty and students' perceptions regarding the content of a graduate professional seminar in communication. Results indicate that students would prefer a focus on implicit norms and the hidden curriculum, while faculty would prefer to focus on disciplinary content. We offer recommendations for developing a course that addresses both needs and, thus, simultaneously attends to the changing job market.